Complementarity And Substitution Between The Neoclassical And Endogenous Growth Theories - Azzouz, Younes; Ben Dehina, Meryem (Université de M'sila, 2017)
This article attempts to define the process of complementarity and substitution between the Neoclassical and Endogenous Growth Theories. Certainly the latter based on the results of the former and tried to complete it, but they brought many radical changes, especially in regard of the origin of technical progress and releasing the assumption of perfect competition.
Keywords: Neoclassical Theory, Endogenous Growth, Steady-state